Source localization of the visual C1 ERP component - Raid, Mohammed Fatin; Begum, Tahamina; Reza, Mohammed Faruque (Bangladesh Journal of Medical Science, 2023)
Background: Although some studies of the C1 ERP component have revealed perceptual variation in pregnant women, source localization has not yet been determined in this group. We aimed to investigate the source localization of the C1 component in pregnant women using the sLORETA tools in Net Station software. Method: A total of 36 participants were recruited and divided between the control (n=18) and pregnant group (n=18). ERP data were collected using 128 ERP nets during a visual oddball paradigm (standard: O and target: X). Grand average waveforms were entered into the Geosource system using sLORETA tools in Net Station software. MRI images were displayed automatically in sLORETA to show the source of the C1 ERP component for both groups. Results: The control group showed that standard stimuli activated Brodmann area 18 in the inferior occipital gyrus in the occipital lobe and target stimuli activated area 11 in the rectal gyrus in the frontal lobe. The pregnant group showed that standard stimuli activated Brodmann area 11, which consists of the medial frontal gyrus in the frontal lobe, and target stimuli activated area 10, which is in the medial frontal gyrus in the frontal lobe. Conclusion: The source of the C1 ERP component was in the frontal lobe for pregnant women during both standard and target stimuli as they used their encoding and executive function areas for attentional purposes. Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 398-402